Integrasi Ilmu dan Agama: Praktik Islamisasi Ilmu Pengetahuan Umum di Perguruan Tinggi - Nugraha, Muhamad Tisna (Al-Hikmah: Jurnal Agama dan Ilmu Pengetahuan, 2020)
This research aims to describe the practice of integration science and religion in Islamic Religious Colleges or Perguruan Tinggi Keagamaan Islam (PTKI), and various obstacles in realizing it. For that reason, researcher used library research (qualitative library research) with qualitative methods to get research conclusions. The data collection of this study, used instruments of observation and documentation techniques. Based on the the library research result, the conclusions are: 1) Integration of science and religion is implemented with different interpretations in each PTKI. 2) the percentage of general knowledge and religious education content is not proportional with PTKI. 3). It is not known certainty the number of research and community service practices by lecturers with general expertise and lecturers with ​​religious expertise, so are as collaboration between the two as both and the standards for the achievement of those goals.